Electron energy probability function and dust charge in the temporal afterglow of a plasma with large dust density - Denysenko, I.B.; Ivko, S.; Azarenkov, N.A.; Burmaka, G. (Вопросы атомной науки и техники, 2018)
Analytical expressions for the electron energy probability function (EEPF) in an argon plasma afterglow with
large dust density, which are obtained from the homogeneous Boltzmann equation for different steady-state EEPFs
(including both Maxwellian and Druyvesteyn distributions at electron energies larger than the dust-surface potential), are presented. The casewhen the rate for electron-neutral momentum-transfer collisions is independent of the
electron energy is considered. It is analyzed how the EEPF shape depends on the afterglow time and the decay time
of dust charge. It is also found how the decay time of dust charge depends on the decay time of effective electron
temperature and that of electron density. The conditions when the energy derivative of the EEPF may be positive are
obtained. Представлено аналітичні вирази для функції розподілу електронів за енергією (ФРЕЕ) в аргоновій плазмі з
великою густиною пилових частинок, що є в режимі післясвітіння. Вирази отримано з однорідного рівняння
Больцмана для електронів з різними початковими ФРЕЕ (включно з розподілами Максвелла та Дрюйвестейна
за енергій електронів, які є більшими за потенціальну енергію поверхні пилових частинок). Розглянуто випадок, коли частота пружних зіткнень електронів з атомами аргону не залежить від енергії електронів. Проаналізовано, як форма ФРЕЕ залежить від часу післясвітіння плазми та часу, що характеризує зменшення заряду
пилових частинок. Знайдено також, як час, що характеризує зменшення заряду пилових частинок, залежить від
часів, що характеризують спадання ефективної температури та густини електронів. Знайдено умови, коли похідна ФРЕЕ за енергією може бути додатною. Представлены аналитические выражения для функции распределения электронов по энергии (ФРЭЭ) в аргоновой плазме с большой плотностью пылевых частиц в режиме послесвечения. Выражения получены из однородного уравнения Больцмана для электронов в случае разных начальных ФРЭЭ (включая распределения
Максвелла и Дрюйвестейна при энергиях электронов больших чем потенциальная энергия поверхности пылевых частиц). Рассмотрен случай, когда частота упругих столкновений электронов с атомами аргона не зависит
от энергии электронов. Проанализировано, как форма ФРЭЭ зависит от времени послесвечения плазмы и времени, характеризующего уменьшение заряда пылевых частиц. Найдено также, как время, характеризующее
уменьшение заряда пылевых частиц, зависит от времен, характеризующих спадание эффективной температуры
и плотности электронов. Найдены условия, когда производная ФРЭЭ по энергии может быть положительной.